Programmed Cell Death 10 Mediated CXCL2-CXCR2 Signaling in Regulating Tumor-Associated Microglia/Macrophages Recruitment in Glioblastoma - Zhang, Quan; Wang, Junwen; Yao, Xiaolong; Wu, Sisi; Tian, Weidong; Gan, Chao; Wan, Xueyan; You, Chao; Hu, Feng; Zhang, Suojun; Zhang, Huaqiu; Zhao, Kai; et al. (Frontiers in Immunology, 2021)
Background Programmed cell death 10 (PDCD10) plays a crucial role in regulating tumor phenotyping, especially in glioblastoma (GBM). Tumor-associated microglia/macrophages (TAMs) in tumor pathological microenvironment contribute to GBM progression. We previously found that the infiltration of TAMs was associated with PDCD10 expression in GBM patients. Thus our study aims to further explore the functional regulation of PDCD10 in GBM on TAMs. Methods Overexpression of PDCD10 in human- and murine-GBM cells was established by lentiviral transduction. Cell behaviors and polarization of TAMs were investigated through indirect co-culture with GBM cells in vitro. The PDCD10-induced release of chemokines was identified by a chemokine protein array. The cross-talk between GBM and TAMs was further studied using selective antagonist SB225002. Finally, an orthotopic homograft mouse model was employed to verify the results of in vitro experiments. Results Indirect co-culture with PDCD10-overexpressed GBM cells promoted proliferation, migration and pro-tumorigenic polarization of TAMs. Pdcd10-upregulated GBM cells triggered a nearly 6-fold increase of CXCL2 release, which in turn activated CXCR2 and downstream Erk1/2 and Akt signaling in TAMs. The blockage of CXCR2 signaling with specific inhibitor (SB225002) abolished TAMs migration induced by PDCD10-upregulated GBM cells. Moreover, Pdcd10-upregulated GL261 cells promoted TAM recruitment and tumor growth in vivo. Conclusion Our study demonstrates that overexpression of PDCD10 in GBM recruits and activates TAMs, which in turn promotes tumor progression. CXCL2-CXCR2 signaling mediated by PDCD10 is potentially involved in the crosstalk between GBM cells and TAMs.